Large Cell Calcifying Sertoli Cell Tumor with Macrocalcification in a Partially Resected Testis - Mahmoud Bardisi; Mohamad Nidal Khabaz; Jaudah Ahmad Al-Maghrabi (Case Reports in Pathology, 2020)
Large cell calcifying Sertoli cell tumors (LCCSCTs) are extremely rare, with less than 100 tumors being described to date. Most of the tumors are benign with a few malignant cases, and aggressive behavior is infrequent. These tumors are a type of Sertoli cell tumor, and these tumors comprise less than 0.3% of all testis tumors in Saudi Arabia. They usually occur in boys and young adults and can affect one or both testicles in multifocal form causing microcalcifications. A 28-year-old male visited our hospital with left testis pain. Physical examination of the scrotum revealed that both testicles were normal sized with no palpable mass. Ultrasonography evaluation revealed grade 3 left varicocele and an incidental 9 mm calcified mass in the right testicle, which was further confirmed by MRI. Partial orchiectomy was performed. Clinical data, radiological studies, and morphological and immunohistochemical characteristics were analyzed.